2017
DOI: 10.1093/jamia/ocx077
|View full text |Cite
|
Sign up to set email alerts
|

Association between workarounds and medication administration errors in bar-code-assisted medication administration in hospitals

Abstract: In hospitals using barcode-assisted medication administration, workarounds occurred in 66% of medication administrations and were associated with large numbers of medication administration errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 42 publications
1
66
0
1
Order By: Relevance
“…These findings echo the growing body of work exploring workarounds within health care settings, as well as the tensions among workarounds as a threat to patient safety and as a means of overcoming systemic shortcomings and resource constraints [ 28 , 29 , 35 ]. For example, a recent study of workarounds in hospital electronic prescribing systems found workarounds as a result of time pressures induced by learning new technological systems as well as increasing demands and duties tasked to clinic staff [ 28 ].…”
Section: Discussionmentioning
confidence: 52%
“…These findings echo the growing body of work exploring workarounds within health care settings, as well as the tensions among workarounds as a threat to patient safety and as a means of overcoming systemic shortcomings and resource constraints [ 28 , 29 , 35 ]. For example, a recent study of workarounds in hospital electronic prescribing systems found workarounds as a result of time pressures induced by learning new technological systems as well as increasing demands and duties tasked to clinic staff [ 28 ].…”
Section: Discussionmentioning
confidence: 52%
“…24 As with most CDSS, errors can still be made if providers omit or deliberately work around the technology. 27 CDSS also improve patient safety through reminder systems for other medical events, and not just those that are medication related. Among numerous examples, a CDSS for blood glucose measurement in the ICU was able to decrease the number of hypoglycemia events.…”
Section: Functions and Advantages Of Cdss Patient Safetymentioning
confidence: 99%
“… 41–43 Recent studies also report high rates of false positive alerts using a BCMA system, which could contribute to alert fatigue and increase workarounds during medication administrations. 44 , 45 Although BCMA has been widely adopted and a small number of dose alert systems have been integrated into clinical environments to facilitate real-time error prevention, 4–6 , 19 , 21 , 28 , 29 few have measured the impact on harm mitigation subsequent to medication safety events. 8 , 46 As described in our earlier research, 25 , 26 rather than using static formulas and barcoding technology, we developed a set of computerized algorithms to analyze dynamic EHR content to identify MAEs.…”
Section: Background and Significancementioning
confidence: 99%